Providing compassionate care in a virtual context: Qualitative exploration of Canadian primary care nurses’ experiences - Rouleau, Geneviève; Wu, Kelly; Parry, Monica; Richard, Lauralie; Desveaux, Laura (Digital health, 2024)
Objective Virtual care presents a promising opportunity to create new communication channels and increase access to healthcare. However, concerns have been raised around the potential for unintended emotional distances created through virtual care environments that could strain patient–provider relationships. While compassionate care is an enabler of emotional connectivity and a core tenant of nursing, little is known about whether or how nurses have adapted their compassion skills into virtual interactions. These concerns are particularly relevant in primary care, where there is a focus on relational continuity (i.e. relationship-based, longitudinal care) and a broad uptake of virtual care. The aim of this study was to explore the meaning of compassionate virtual care and to uncover how nurses operationalized compassionate care through virtual interactions in primary care. Methods We used a qualitative interpretive descriptive lens to conduct semistructured interviews with primary care nurses (Ontario, Canada) who had provided virtual care (i.e. video visits, remote patient monitoring, or asynchronous messaging). We used a thematic approach to analyze the data. Results We interviewed 18 nurse practitioners and two registered nurses. Participants described how: (1) compassionate care was central to nursing practice, (2) compassionate care was evolving through virtual nurse–patient interaction, and (3) nurses balanced practice with patients’ expectations while providing virtual compassionate care. Conclusions There is an opportunity to better align nurses’ understanding and operationalization of compassionate care in virtual primary care contexts. Exploring how compassionate care is operationalized in primary care settings is a necessary first step to building compassionate competencies across the nursing profession to support the continued virtual evolution of health service delivery.